Strategi Pemasaran Melalui Media Sosial : Studi Kasus Pada Isma Ayam Penyet - Yunita, Ardianti; Aini, Nurtina; Pardede, Jessica Angalina Putri; Purba, Nadila Sapria; Sitorus, Pebrina; Pakpahan, Pesta Juliana; Artika, Rindi; Nirwana, Suci; Purba, Rakhmawati; Siahaan, Rumiris (STIE Bina Karya, 2025)
This research aims to analyze the social media marketing strategies used by Isma Ayam Penyet and provide recommendations for development based on field findings. This research is a qualitative study with a case study approach involving in-depth interviews. The analysis results show that Isma Ayam Penyet implements three main strategies, namely marketing through Facebook with simple content, word-of-mouth marketing, and WhatsApp for delivery services. It has been proven that these strategies increase brand awareness and expand market reach, but they have limitations in terms of content variation and platform diversification. Based on this analysis, this research suggests enhancing digital marketing effectiveness by developing a multi-platform strategy, improving content quality, and optimizing customer engagement